Muhammad Abdul Jabbar Beg: Arabic Loan-Words in Malay. A Comparative Study (A Survey of Arabic and Islamic Influence upon the Languages of Mankind), The University of Malaya Press, Pantay Valley, Kuala Lumpur, 3a edición, 1983, XX + 251 pp. - Chuaqui, Rubén (Estudios de Asia y África, 1989)
-